School Meals and Food Poverty: Children's Views, Parents' Perspectives and the Role of School. (5th June 2019) - Cardoso, Sónia Goulart; Truninger, Mónica; Ramos, Vasco; Augusto, Fábio Rafael
Abstract : This paper addresses the importance of school meals in balancing food budgets and diets among 45 low‐income families in Portugal. Drawing on interviews with both parents and children (aged 11–15 years) we found that children's views on the quality of school meals affect their willingness to eat at school and heighten parental concerns with health, food and resources. For parents, school meals are crucial to ensure children's dietary variety and balancing tight food budgets. Schools' role in food poverty alleviation is also critically addressed, contributing to current and future sociological studies of children, school meals and food poverty.